Analyse de la jonction compétences individuelles et compétences collectives : Proposition d’un plan mitigation des impacts Covid- 19 - BARGACH, Khalid; LALAOUI , Siham (Revue Internationale du Chercheur, 2021)
Today, collective competence is no longer an option, but rather an imperative in the face of unexpected crises. The impacts of the COVID-19 pandemic exposed the insufficiencies of individual skills to manage uncertainties. Collective competence as a source of added value, results in the combination of individual skills of a collective of work to face a situation that could not be assumed by each of its members alone. To negotiate the unforeseen events generated by COVID-19, managers will need an explicit matrix of individual skills in addition to the conditions required for the combination of these skills. However, is this notion of collective competence well defined by scientific research? how to improve the interconnections between the elements of the collective to combine them effectively? ... There are so many questions that will be addressed in this research, by mobilizing the related theoretical framework. The analysis of these theories conveys that the variables characterizing individual skills cannot respond to the interaction required to face the crisis and that the link between individual skills and collective skills has remained weakly explored to date. In our research, we propose a skills plan for the mitigation of the impacts of COVID-19, integrating the variables of individual skills and their links with the variables conditioning the combination of these skills.